THE ROLE OF WOMEN IN MARITAL DYNAMICS: Hadis Interpretation of Amina Wadud’s Hermeneutic - Saputri, Rahmah Eka; Burhanuddin, Nunu; Gazali, Gazali; Hendri, Novi; Majid, Mariam Abd. (State Islamic University North Sumatra, 2024)
Abstract: Misogynist views emerged from gender-insensitive reading of hadiths that talk about women, are often used as legitimacy in perpetuating injustice and even violence against women in the domestic sphere. The hadith misinterpreted as a justification for a husband's authority over his wife is the hadith regarding women's service to their husbands. In this regard, this article attempts to dig up in-depth information regarding the hadith, by taking a hermeneutic approach in re-understanding the hadith. This research aims to create a new meaning that is not misogynistic, by referring to the feminist hermeneutic method offered by Amina Wadud. This research uses library methods to explore relevant information through books and journals. The results of this research show that although the concept of submissive marriage was the social context in which this hadith was born, practically, the Prophet never showed an authoritative attitude towards his wife.Keywords: Misogynist hadith, women's service, feminist hermeneutics, Amina Wadud, gender studies.